User Experience Analysis of Satisfaction of Job Seekers (PENCAKER) in the City of Semarang Manpower Department in Using the SIKER Application Using the User Experience Questionnaire (UEQ) Method (Universitas Negeri Semarang, 2021)
The Semarang City Manpower Service or also known as (DISNAKER) is a government agency that can foster and control the manpower sector. The Manpower Office has its website application, namely the work system (SIKER) which is an integrated employee recruitment information system from the Semarang city government, companies, and also the community or job seekers. This study aims to understand the level of comfort in terms of User Experience in using the SIKER application. Analysis of the SIKER website application by applying the User UEQ method approach given to 32 respondents who have used this website. The UEQ assessment focuses on six aspects, namely: efficiency, attractiveness, accuracy, clarity, novelty, and stimulation. The results obtained after conducting the analysis are that the average respondent gives below average results, at the User Experience level the efficiency item gets a sufficient value, on the clarity, accuracy, stimulation, attractiveness, and novelty scales it gets a value below the average. This tends to be the lack of seeker users with this SIKER application. In other words, the reason is that there are still many users who don't understand this application because this application is still relatively new.